DETERMINANTS OF SMES’ SUSTAINABLE DEVELOPMENT: A SYSTEMATIC LITERATURE REVIEW - DURA CODRUȚA CORNELIA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
There is growing concern that the Sustainable Development Goals (SDGs) may not be achieved within the proposed timeline, partly due to the insufficient focus on the sustainable development of small and medium-sized enterprises (SMEs). SMEs play a pivotal role in the global economy but are often overlooked in sustainability initiatives. To address this gap, this study conducted a systematic literature review to map existing research on SMEs sustainable development. The PRISMA framework was adopted for this study. Scopus was utilized to identify relevant literature, covering a 10-year period from 2015 to 2024. Data analysis was conducted using Microsoft Excel for descriptive analysis and SPSS (version 25) for literature classification. The review revealed a growing interest in SMEs sustainability, with research in this area gradually increasing. The study identified seven primary drivers of SMEs' sustainable development: societal influence, regulatory pressure, sustainable finance, corporate culture, cost savings, digitalization, and bricolage.